The Media and Subnational Authoritarianism in Papua. (September 2015) - Tapsell, Ross
This article examines the hindrances to journalists' autonomy in the Papua provinces of Indonesia. It argues that media practitioners in Papua are operating in a subnational authoritarian environment, where the freedoms enjoyed by journalists elsewhere in Indonesia's largely robust media are not afforded to local journalists. The article explains that security forces and local government are the main factors influencing mainstream news content in the region. Yet, as Internet penetration rises and new communication technologies are advanced, new online journalism ventures are gaining in prominence. Their success will depend on whether subnational authoritarianism remains the status quo in a region where new local media ventures are largely unable to provide open and critical coverage of events and issues.